The effects of acetylsalicylic acid on performance, carcass traits, breast meat quality and white striping muscle defects in broiler chickens - Gungoren, Gulsah; Simsek, Ulku Gulcihan; Gungoren, Alper; Ciftci, Mehmet; Eroksuz, Hatice; Karabulut, Burak; Top, Sermin (Wiley, 2025)
BACKGROUNDThis research aims to reduce white striping muscle defects induced by vascular inflammation and hypoxia using the anti-inflammatory, antiplatelet and anti-atherothrombotic properties of acetylsalicylic acid (ASA). To this end, the effects of different doses (0.3, 0.6, 1, 3 and 6 g L-1) of ASA added to drinking water at 24-48 days on growth performance, carcass traits, footpad dermatitis, white striping and breast meat quality parameters were investigated.RESULTSThe results indicate that 0.3, 1, 3 g L-1 and especially 0.6 g L-1 ASA treatment significantly improved growth performance and meat quality parameters. Also, doses of 0.3, 6 g L-1 and especially 0.6 g L-1 of ASA treatment reduced the incidence of white stripe muscle defects.CONCLUSIONSConsequently, 0.6 g L-1 ASA treatment reduced macrophage infiltrations and myodegeneration caused by growth rate. In addition, this dose increased vascular endothelial growth factor and decreased irisin level in breast muscle. The study also shows that high doses of ASA treatment (3 and 6 g L-1) may make footpad dermatitis more common. This may be due to the fact that ASA can cause side effects such as gizzard ulcers and kidney damage in broiler chickens. (c) 2025 The Author(s). Journal of the Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: white striping; meat quality; irisin; aspirin; defect; VEGF